212k views
0 votes
Pls Help, Max Points

Pls Help, Max Points-example-1
User BigMiner
by
5.4k points

2 Answers

6 votes


\\ \rm\Rrightarrow (2)/(x+3)-(1)/(x-3)=(-7)/(x^2-9)


\\ \rm\Rrightarrow (2(x-3)-1(x+3))/((x+3)(x-3))=(-7)/(x^2-9)


\\ \rm\Rrightarrow (2x-6-x-3)/(x^2-9)=(-7)/(x^2-9)


\\ \rm\Rrightarrow (x-9)/(x^2-9)=(-7)/(x^2-9)


\\ \rm\Rrightarrow x-9=-7


\\ \rm\Rrightarrow x=9-7


\\ \rm\Rrightarrow x=2

User Olivier Royo
by
5.0k points
11 votes

Answer:

x = 2

Explanation:


\large \begin{aligned}(2)/(x+3)-(1)/(x-3) & = (-7)/(x^2-9)\\\\(2(x-3))/((x+3)(x-3))-(1(x+3))/((x+3)(x-3)) & = (-7)/((x+3)(x-3))\\\\(2(x-3)-(x+3))/((x+3)(x-3)) & = (-7)/((x+3)(x-3))\\\\(x-9)/((x+3)(x-3)) & = (-7)/((x+3)(x-3))\\\\x-9 & = -7\\\\x&=-7+9\\\\x & = 2\end{aligned}

User Kriver
by
5.6k points